Perlindungan Lahan Pertanian Pangan Berkelanjutan dalam Perspektif Penatagunaan Tanah di Kota Gorontalo - Nurul Magfirah, Nia; Junus, Nirwan; Rivaldi Moha, Mohamad (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2025)
The increasingly rampant conversion of agricultural land in Gorontalo City poses a threat to the sustainability of Sustainable Food Agricultural Land (LP2B), so a legal study is needed from a land use perspective. This study aims to analyze the protection of Sustainable Food Agricultural Land (LP2B) in Gorontalo City from a land use perspective. This study uses an empirical legal approach with qualitative methods, through interviews with technical agencies and farmers and analysis of policy documents. The results show that LP2B protection in Gorontalo City has not been optimally implemented due to the absence of specific regional regulations that regulate LP2B protection in detail. This regulatory weakness is exacerbated by the vulnerable socioeconomic conditions of farmers, high urban development pressures, and weak inter-agency coordination in monitoring and controlling land use conversion. Although there are land replacement policies and outreach to farmers, these steps have not been able to address the structural challenges of LP2B protection. Therefore, it is necessary to formulate regional regulations on LP2B protection, integrate spatial data into the RTRW (Regional Spatial Plan), strengthen land use monitoring, and provide incentives to agricultural actors to maintain food security and agrarian sustainability in Gorontalo City.